(untitled) (American Journal of Arts and Human Science, 2025)
Malnutrition is a major threat to children in the Philippines, with approximately ninety-five (95) children dying daily due to related causes. This study highlights the urgent need for effective interventions, such as the Gulayan sa Paaralan Program which aims to promote food security and improving nutrition among school children. Specifically, it sought to assess the respondents’ characteristics, examine the respondent’s level of challenges in the implementation of the Gulayan sa Paaralan, and test the significant relationship between the respondents’ challenges of the Gulayan sa Paaralan Program (GPP). The researcher identified one hundred fifty (150) Edukasyong Pantahanan at Pangkalusugan teachers from elementary schools in the Cagayan de Oro City division. An adopted survey questionnaire was used, covering sections on respondents’ characteristics, challenges, and interventions. The descriptive-correlational survey method was employed to analyze program implementation data. Descriptive statistics such as percentage, mean, standard deviation, and Person Product Moment Correlation were used for data analysis. The findings showed that the majority of teacher respondents were Teacher 1’s who took significant roles in the Gulayan sa Paaralan Program implementation. Moreover, the level of challenges indicated that in program management, inadequate resources, and weak partnerships significantly hindered the program’s success, with community engagement emerging as a crucial area for improvement. Further, to enhance the effectiveness of the program, fostering community ties and securing sustainable funding is essential. It is recommended that teachers engage in professional development, school administrators allocate more resources, the Department of Agriculture provides targeted training, and future researchers explore best practices in agricultural education.